2020
DOI: 10.3389/fmicb.2020.00874
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequencing of Hepatitis A Virus Using a PCR-Free Single-Molecule Nanopore Sequencing Approach

Abstract: Hepatitis A virus (HAV) is one of the most common causes of acute viral hepatitis in humans. Although HAV has a relatively small genome, there are several factors limiting whole genome sequencing such as PCR amplification artefacts and ambiguities in de novo assembly. The recently developed Oxford Nanopore technologies (ONT) allows single-molecule sequencing of long-size fragments of DNA or RNA using PCR-free strategies. We have sequenced the whole genome of HAV using a PCR-free approach by direct reverse-tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…NGS can be optimized for rapid sample preparation and real-time sequence analysis, as well as the rapid identification of certain pathogens [ 42 , 43 , 44 , 45 , 46 , 47 ]. Amplicon-based NGS sequencing is an increasingly preferred method in the rapid detection and genomic characterization of specific pathogens, with high specificity and sensitivity [ 48 , 49 , 50 , 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…NGS can be optimized for rapid sample preparation and real-time sequence analysis, as well as the rapid identification of certain pathogens [ 42 , 43 , 44 , 45 , 46 , 47 ]. Amplicon-based NGS sequencing is an increasingly preferred method in the rapid detection and genomic characterization of specific pathogens, with high specificity and sensitivity [ 48 , 49 , 50 , 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Long-read sequencing platforms can generate reads spanning the length of these sgRNA and are thus better suited to transcriptomic characterization of its highly nested transcriptome. One such platform is the MinION (Oxford Nanopore Technologies [ONT]), which can sequence either native RNA or cDNA directly without requirement for PCR amplification, therefore reducing PCR-induced biases in estimation of expression levels (Garalde et al, 2018;Batista et al, 2020). Furthermore, RNA modifications induce changes in ONT signal, which enable exploration of the epi-transcriptome using direct RNA (dRNA) sequencing (Garalde et al, 2018;Kim et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was reported that 382 nucleotides of the SARS-CoV-2 genome had been deleted in Singapore, which was caused by false-negative reports when target sequences were defined based on deleted region [126]. Recently, singlemolecule nanopore (SMN) sequencing or third-generation platform was developed by Oxford Nanopore Technologies (ONT), which makes it possible to sequence long-size fragments of DNA/RNA [127]. SMN technique can detect changes in the nucleotides of DNA and RNA strand by passing them through a nanopore protein, which results in the production of a detectable electrical signal.…”
Section: Nanobiomaterial-based Biosensors For the Diagnosis Of Covid-19mentioning
confidence: 99%
“…SMN technique can detect changes in the nucleotides of DNA and RNA strand by passing them through a nanopore protein, which results in the production of a detectable electrical signal. Recently, SMN sequencing for detecting Hepatitis C [128], Hepatitis A [127], and Influenza virus A [129] were reported. However, because SMN is more time-consuming than other POC platforms, it is not currently considered a primary method for detecting SARS-CoV-2.…”
Section: Nanobiomaterial-based Biosensors For the Diagnosis Of Covid-19mentioning
confidence: 99%